1984
DOI: 10.1002/jcp.1041200316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and partial purification of keratinocyte growth factor from the hypothalamus

Abstract: An extract of bovine hypothalamus is known to be mitogenic for human keratinocytes in vitro. In order to identify the responsible substance(s), biochemical characterization and subsequent bioassay of the extract in a serum-free culture system were performed. The keratinocyte growth-promoting activity of the hypothalamic extract was unaffected by heating (100 degrees C, 10 min); acidification to pH 3.3; or by exposure to lipase, RNAase, or proteolytic enzymes; but was abolished by alkalinization to pH 11. An ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…However, one important trend was the increase of the diffusional exponent with increasing PEGdA content. With the assumption that increasing PEGdA content would lead to increased degree of crosslinking, the results in this study corresponded well with others' findings (15). The power law exponent with varying gelatin content did not show any noticeable trend which made these material systems particularly interesting for further study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, one important trend was the increase of the diffusional exponent with increasing PEGdA content. With the assumption that increasing PEGdA content would lead to increased degree of crosslinking, the results in this study corresponded well with others' findings (15). The power law exponent with varying gelatin content did not show any noticeable trend which made these material systems particularly interesting for further study.…”
Section: Resultssupporting
confidence: 92%
“… a taken from (12) b taken from (13) c taken from (14) d taken from (15) e taken from (16) f pKa g isoelectric point …”
Section: Figmentioning
confidence: 99%
“…It also strongly suggests that the keratinocyte growth factor present in crude brain extract known to contain endothelial cell growth factor activity (Gilchrest et al, 1984) could, in fact, be aFGF. Finally, the recent report that a newly isolated and potent keratinocyte growth factor produced by M 426 fibroblast has significant homology to the other five known members of the FGF family (Rubin et al, 1989) agrees with the fact that FGF itself is mitogenic for keratinocytes.…”
Section: Previous Studies Have Shown That Mk Cells Dependmentioning
confidence: 97%
“…In 1984, an extract of hypothalamus led to the partial purification and characterization of a mitogen factor, termed keratinocyte growth factor [79,80], because of its predominant activity on this cell type. The complementary DNA sequence of KGF demonstrated that it is a member of the FGF family [81], FGF-7.…”
Section: Fgf-7mentioning
confidence: 99%